The Influence of Learning Models and Student Interest on Learning Outcomes of Physical Fitness at SMP Negeri 35 Palembang - Lesmana, Anggra (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the effect of learning models and student interest on learning outcomes of Class VII students at Junior High School 35 Palembang on physical fitness material. The population in this study were all class VII students of Junior High School 35 Palembang consisting of 7 classes with a total of 137 students for the 2023/2024 school year, 62 female students and 75 male students. Determination of the sample using random and selected class VII.5 and VII.6. This research is a quasi-experimental study using a 2 x 3 factorial design with data collection techniques through student interest questionnaires and learning achievement tests. The data obtained were analyzed using descriptive statistical analysis and inferential statistical analysis using Two Way Anova with an error rate of 5% (= 0.05). The results of the descriptive statistical analysis obtained that the average value of the learning outcomes of students who were taught with the PBL learning model was higher than the PJBL learning model. The results of inferential statistical analysis show that (a) the learning model influences the learning outcomes of class VII students of Junior High School 35 Palembang; (b) interest in learning affects the learning outcomes of class VII students of Junior High School 35 Palembang; (c) There is no interaction between the learning model and student interest in influencing the learning outcomes of class VII students of Junior High School 35 Palembang.